"The Effect of the T.A.S.C Model on Scientific Alertness Among Fifth Grade Female Pupils in Science Subject" (Journal of the College of Basic Education, 2025)
The research aims to identify the effect of the T.A.S.C model on the scientific alertness of fifth-grade female pupils in the subject of science by verifying the following hypothesis:There is no statistically significant difference at the level of (0.05) between the mean scores of the experimental group pupils who will study science according to the T.A.S.C model and the mean scores of the control group pupils who will study the same subject using the traditional method on the scientific alertness scale.The researchers adopted a quasi-experimental design with two groups (experimental and control) using a post-test only for achievement. The research population consisted of public (daytime) elementary schools for girls in Babil Governorate for the academic year 2024–2025. A purposive sample was selected from "Usama bin Zaid Elementary School for Girls," consisting of (88) female pupils divided into two groups: (43) in the experimental group and (45) in the control group .The two groups were equalized based on the following variables: chronological age of pupils (in months), parents’ educational attainment, intelligence (Raven’s test), mid-year science scores, and prior knowledge. The experiment was conducted during the second semester of the 2024–2025 academic year. A total of (157) behavioral objectives and (32) lesson plans were prepared for each group. A scientific alertness scale consisting of (32) items was developed and was validated and confirmed to be reliable. The statistical tools used included: Pearson’s correlation coefficient, t-test, item difficulty and discrimination indices, the equivalent forms method, test-retest method, and Cronbach’s alpha coefficient. After completing the experiment, the scientific alertness scale for the science subject was administered. The results showed that the experimental group outperformed the control group on the scientific alertness scale. Based on these findings, conclusions, recommendations, and suggestions were presented.